Comparative Study of Staphylococcus epidermidis Virulence Profiles in an animal Model of Endophthalmitis - Samudio, Margarita; Abente, Sonia; Villalba, Vanesa; Penniecook, Jason; González, Emilio; Schinini, Alicia; Figueredo, Susy; Duré, Carolina; Mino de Kaspar, Herminia (Medicina Clínica y Social, 2024)
Introduction: Gram-positive staphylococci are responsible for over 90% of cases of postoperative infectious endophthalmitis, with Staphylococcus epidermidis accounting for approximately 70% of isolated microorganisms. Objective: To evaluate the relationship between S. epidermidis virulence and severity of endophthalmitis in an animal model. Methodology: New Zealand albino rabbits were divided into two groups and administered 100 colony-forming units of S. epidermidis strains. In the virulent group, four rabbits received a multi-antibiotic resistant, mecA, ica, and atlE gene carrying S. epidermidis strain, from a patient´s conjuntival microbiota and three a biofilm-forming S. epidermidis ATCC 35984. In the non-virulent group, five rabbits were inoculated with a strain sensitive to all tested antibiotics and lacking mecA, ica, and atlE genes, also from a patient and three rabbits received the non-producer biofilm S. epidermidis ATCC 29122. Clinical and ultrasound examinations were conducted every three hours until endophthalmitis symptoms appeared, followed by daily clinical assessments. Histological evaluations were performed 15 days post-inoculation. Results: The less virulent group displayed milder inflammation and reduced intraocular damage in comparison to the more virulent group based on clinical and ultrasound observations. Nevertheless, histopathological analysis revealed similar inflammation in all groups, 15 days post-inoculation. Discussion: Less virulent S. epidermidis strains induced less severe inflammation as observed through clinical and ultrasound assessments. However, long-term histopathological assessments showed effects comparable to those seen with the more virulent strain.